(untitled) (Global Journal of Human-Social Science, 2014)
Research into factors and theories of cooperation and into managing relations between human communities and ecosystems has blossomed in recent decades, yet few published works examine how these advances may be conveyed to students of resource and environmental management. We question whether ongoing changes in sociocultural and biophysical environments will lead to selfperpetuating crises or to precedent-setting types and scales of cooperation? Will higher education and university curricula continue to be part of our ’environmental problem’ or emerge as essential parts of responses to the failure of resource management institutions? Are graduate students in environmental fields being prepared to meet the challenges they will likely face as resource management researchers and decision makers? We examine these questions through the lens of a course we have taught to over 300 graduate students in Simon Fraser University’s School of Resource and Environmental Management. The course emphasizes the acquisition and application of conceptual and practical knowledge and skills centered on cooperation among individuals and groups with diverse values and interests.